2007
DOI: 10.1007/s12079-007-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of the PI3-kinase/mTor pathway in the regulation of the stearoyl CoA desaturase (SCD1) gene expression by insulin in liver

Abstract: The stearoyl-CoA desaturase 1 (SCD1) catalyzes the synthesis of monounsaturated fatty acids. This enzyme is a critical control point regulating hepatic lipogenesis and lipid oxidation. Therefore SCD1 may be a potential therapeutic target in the treatment of obesity and metabolic syndrome. Regulation of SCD1 expression occurs primarily at the level of transcription. In the present study, we characterized the insulin response elements (IREs) and the insulin signaling pathway mediating the regulation of SCD1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 66 publications
10
51
0
Order By: Relevance
“…The conclusion that mTORC1 is required for insulinmediated SREBP-1c induction in liver is consistent with previous findings in retinal pigment epithelial cells by Porstmann, et al (19), who showed that rapamycin blocks the increase in SREBP-1c protein that is induced by activation of Akt in these nonhepatic cells. The results are also consistent with the findings of Mauvoisin, et al (26), who showed that rapamycin blocks the induction of SCD-1, an SREBP-1c target gene, in chicken embryo hepatocytes. All of these results differ from the finding of Azzout-Marniche, et al (27), who failed to find an inhibitory effect of rapamycin on insulin-mediated increases in SREBP-1c mRNA and membrane-bound SREBP-1c protein in freshly isolated rat hepatocytes.…”
Section: Discussionsupporting
confidence: 92%
“…The conclusion that mTORC1 is required for insulinmediated SREBP-1c induction in liver is consistent with previous findings in retinal pigment epithelial cells by Porstmann, et al (19), who showed that rapamycin blocks the increase in SREBP-1c protein that is induced by activation of Akt in these nonhepatic cells. The results are also consistent with the findings of Mauvoisin, et al (26), who showed that rapamycin blocks the induction of SCD-1, an SREBP-1c target gene, in chicken embryo hepatocytes. All of these results differ from the finding of Azzout-Marniche, et al (27), who failed to find an inhibitory effect of rapamycin on insulin-mediated increases in SREBP-1c mRNA and membrane-bound SREBP-1c protein in freshly isolated rat hepatocytes.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that impairment of mTORC1 activity with rapamycin blocks the SREBP-1c induced expression of lipogenic enzymes (24). This is in line with data showing that rapamycin reduces the expression of SREBP-1c target genes such as acetyl-CoA carboxylase (25), fatty acid synthase (26), and stearoyl-CoA desaturase (27). Increased de novo lipid synthesis is an important feature of cancer cells and it is suggested that induction of lipid metabolism by SREBP-1c promotes cancer progression by providing lipids required for membranes.…”
Section: Mtor Inhibitorssupporting
confidence: 79%
“…In vitro studies have shown that mTOR inhibition by rapamycin increases fatty acids b-oxidation in the hepatocytes (25,54) and skeletal muscles (55). In addition, several studies have shown that rapamycin reduces the gene expression of lipogenic enzymes such as acetyl-CoA carboxylase (25), fatty acid synthase (26), and stearoyl-CoA desaturase (27). In addition, rapamycin has been shown to promote fatty acid b-oxidation while decreasing fatty acid flux into anabolic storage pathways in primary cultures of rat hepatocytes, suggesting that the hyperlipidemia associated with rapamycin is not likely due to increased lipid hepatic synthesis but rather due to delayed peripheral clearance (25).…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 99%
“…These observations are consistant with RAPA-induced increases in fatty acid oxidation by increasing activities of carnitine palmitoyltransferases I and II (CPT I and CPT II), which is the primary intracellular regulatory enzyme of the fatty acid oxidation pathway (16). Moreover, decreased fatty liver scores are a result of RAPA inhibition of the mTOR pathway that may also be involved in the regulation of hepatic lipogenesis and lipid oxidation through the regulation of stearoyl-CoA desaturase (34). Thus, RAPA, an mTOR-pathway inhibitor, appears to have had a pronounced effect on body weight by reducing fat pad weight even with a significant increase in food intake, suggesting a specific effect on lipid metabolism.…”
Section: Discussionmentioning
confidence: 98%